PEMBENTUKAN KEPRIBADIAN ANAK MELALUI CERITA KEAGAMAAN - Dhin, Cut Nya (Universitas Islam Negeri Ar-Raniry, 2019)
Religious stories are a method that can be used in educational activities to form a positive personality in students. In fact, there are now many stories that are not based on religious values. Meanwhile, to build a child's personality starts from the baby in the mother’s womb until he is born until he reaches adulthood. So to have a good person there must be start from the family, school and community environment, so that the goals and expectations to educate and teach the children with the values of Islamic, so that the next generation becomes a good person and islamic generation. This research uses the library method with the collection of materials related to the formation of a child's personality through religious stories. Parents as the first educators in the family environment, must provide instructions and direction where the child rests, as well as a teacher in educating his students must use various methods. All of that aims to direct all actions and patterns of thought and behavior or attitudes that will be born in the life of the child.